Conflict prevention among staff - Kosenko, S. A.; Kosenko, A. V. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It is proved that in order for the process of managing labor disputes (conflicts) to be permanent, systemic, it is objectively necessary to create a new such service, which has the status of a state body.
Попередження конфліктів між персоналом
Keywords: conflicts; enterprise personnel; psychology of relations; management